Integration of quantitative precipitation forecasts with real-time hydrology and hydraulics modeling towards probabilistic forecasting of urban flooding. (December 2020) - Brendel, Conrad E.; Dymond, Randel L.; Aguilar, Marcus F.
Abstract: As the world becomes more urbanized and heavy precipitation events increase in frequency and intensity, urban (pluvial) flooding is an emerging concern. Recent advances in hydrologic and hydraulic modeling, high-resolution quantitative precipitation forecasting, and ensemble forecasting have improved the ability to evaluate flash flooding potential in urban areas. The Probabilistic Urban Flash Flood Information Nexis (PUFFIN) app integrates these components into a tool to evaluate the probability of an urban flash flood event and to identify specific infrastructure components at risk. PUFFIN uses a combination of deterministic and probabilistic precipitation forecasts to provide analyses over a range of spatial and temporal resolutions. A case study for the City of Roanoke, Virginia in the United States demonstrates how PUFFIN can be used to assess the risk of urban flooding. However, with minimal modification, the application can be adapted for implementation in other locations. Highlights: Variety of deterministic/probabilistic forecasts and spatial/temporal resolutions. Facilitates evaluation of urban flooding risk at specific infrastructure components. Structure permits implementation in other locations.